2010
DOI: 10.1002/crq.20006
|View full text |Cite
|
Sign up to set email alerts
|

Divorce mediation outcome research: A meta‐analysis

Abstract: Results vary across divorce mediation and litigation outcome studies.Because a quantitative review has never been performed on this body of research, the present study conducts a meta-analysis on this literature. From five studies that met the established inclusion criteria, it was found that mediation produced a grand effect size of 0.36. This smallto-moderate effect size reveals that across the included studies mediation is a beneficial alternative to litigation for divorcing couples. Dependent variables mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 9 publications
4
44
0
4
Order By: Relevance
“…For instance, to date, only one quantitative meta‐analysis comparison of family mediation and litigation has been undertaken, and it comprised merely five studies. This study corroborated that there were moderately better results when family mediation was used instead of divorce litigation in the following areas: children's psychological needs, spousal relationships, and disputants' emotional satisfaction, and their satisfaction with both the process and the outcome (Shaw ). But several reviews of the mediation research have noted the methodological shortcomings of previous comparative studies.…”
Section: Outcome‐based Studiessupporting
confidence: 74%
“…For instance, to date, only one quantitative meta‐analysis comparison of family mediation and litigation has been undertaken, and it comprised merely five studies. This study corroborated that there were moderately better results when family mediation was used instead of divorce litigation in the following areas: children's psychological needs, spousal relationships, and disputants' emotional satisfaction, and their satisfaction with both the process and the outcome (Shaw ). But several reviews of the mediation research have noted the methodological shortcomings of previous comparative studies.…”
Section: Outcome‐based Studiessupporting
confidence: 74%
“…Moreover, these words indicate the active role played by parents in this process: They are directly engaged in the decisions concerning the new organization of their family life, and generally they are involved not only throughout the interview, but also through the use of graphic and symbolic instruments, such as posters and paints. We can hypothesize that these aspects and the methods used have allowed parents to perceive and remember mediation as a specific setting and a relational modality that differs from other experiences: a working group instead of the dependent relationship with the lawyer, the judge, and the psychologist, as well as a logic of reconciliation and transformation instead of a logic of opposition and litigation (Shaw, 2010). This modality might promote personal involvement, activation, assumption of responsibility, and commitment toward himself or herself, the other, the child, and the family relationships in a broader perspective.…”
Section: Downloaded By [Rutgers University] At 21:17 05 April 2015mentioning
confidence: 97%
“…In particular, it turned out to be relevant to recognize not only the legal and practical dimensions of marital dissolution, but also especially the emotional and relational issues involved in the transition of divorce (Beck & Sales, 2001;Shaw, 2010).…”
Section: Downloaded By [Rutgers University] At 21:17 05 April 2015mentioning
confidence: 99%
See 1 more Smart Citation
“…Emery, Otto, and Donahue (2005), in their critique of child custody evaluations, urged that the best solution to child custody disputes was to encourage parents to reach their own decisions about rearing the children after a separation and stated, ''We believe that encouraging private settlement is the best way to promote children's mental health in separation and divorce' ' (p. 20). Supporting this viewpoint, Shaw (2010), in a recent meta-analytic study of divorce mediation, found that mediation has been shown quantitatively to be superior to litigation in dealing with divorce cases. Shaw's study found that mediation had more positive effects than litigation on coparenting relationships and on increasing the parent's understanding of the children's needs, and that mediation participants were more emotionally satisfied than litigation participants.…”
mentioning
confidence: 91%